Structural break and consumer prices: the case of Malaysia - Siti Marsila Mhd Ruslan; Kasypi Mokhtar (Cogent Business & Management, 2020)
This paper studies the dynamic behaviour of both linear and non-linearity of consumer prices in Peninsular Malaysia and Sabah from 2004 to 2015. For linear tests, monthly prices data of consumer price index (CPI) for nine groups of goods and services were analysed using the unit root tests and cointegration tests with structural breaks; while for non-linear test, NARDL test is incorporated. The findings indicated that (i) both Zivot and Andrews unit root test and Perron unit root test provided fairly similar results; most of the breakpoints occurred in 2008, followed by 2012 and 2013, (ii) the variables did not cointegrate in the Johansen cointegration test which indicates that no stable long-run relationship was reflected in the CPI for all groups, except for 'transport', and (iii) the Gregory and Hansen test demonstrated some form of cointegration with a structural break(s) existed, with a most recorded break in 2008 (iv) the NARDL test shows a fair impact of asymmetrical interaction for all groups except for Housing, Water, Electricity, Gas, and Other Fuels; Health and Recreation Services and Culture. Overall, this study intends to match the structural break points and the groups affected with the corresponding critical economic incidents.
Keywords: E3; E5; E6; E7; 650; CPI; structural break; economic policy